2012
DOI: 10.1590/s1516-35982012000500016
|View full text |Cite
|
Sign up to set email alerts
|

Características produtivas e imunológicas de frangos de corte submetidos a dietas suplementadas com cromo, criados sob diferentes condições de ambiente

Abstract: RESUMO -Objetivou-se avaliar o desempenho, a resposta imune e as características de carcaça de frangos de corte alimentados com dietas suplementadas com cromo complexado a levedura (Saccharomyces cerevisae), criados em diferentes condições de temperatura. O experimento foi conduzido em câmaras climáticas com sistema de aquecimento e refrigeração, utilizando-se as seguintes condições de temperatura, de acordo com as idades: 1 a 3 dias (35, 35 e 35 o C ± 2), 4 a 7 dias (35, 30, 25 o C ± 2), 8 a 14 dias (34, 27 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…Lower values of feed intake, weight gain and viability are observed in thermally stressed broilers, especially under high temperature (BOIAGO et al, 2013;OBA et al, 2012). Temperature, relative humidity and wind speed are the major environmental factors affecting animal thermal comfort, providing limits for adequate production (NASCIMENTO et al, 2011;AMARAL et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lower values of feed intake, weight gain and viability are observed in thermally stressed broilers, especially under high temperature (BOIAGO et al, 2013;OBA et al, 2012). Temperature, relative humidity and wind speed are the major environmental factors affecting animal thermal comfort, providing limits for adequate production (NASCIMENTO et al, 2011;AMARAL et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Oba et al (2012) also observed an increase in the thigh + drumstick yield (34.65%) and reduced breast yield (31.98%) in 47-day old broilers kept at 32 °C, compared with those kept at 22 °C.…”
mentioning
confidence: 71%
“…Studies with broilers demonstrated that high temperatures (32 °C) induce a reduction in the size of the most metabolically active organs, in order to reduce the production of body heat, which results in increased carcass ratio:weight after fasting, and consequently, the increase of the carcass yield (OBA et al, 2012;ROSA et al, 2007); however, these changes were not evident in meat quails at 28 or 42 days of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, tais alterações levam à queda de desempenho e do sistema imune das aves (Ribeiro et al, 2008). Diversos estudos mostram a influência negativa do estresse térmico sobre o desempenho de frangos de corte, sendo que o calor é apontado como maior colaborador para tal queda (Laurentz, 2005;Oba, 2012).…”
unclassified